2007
DOI: 10.3201/eid1306.061169
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Spongiform Encephalopathy and Spatial Analysis of the Feed Industry

Abstract: In France, despite the ban of meat-and-bone meal (MBM) in cattle feed, bovine spongiform encephalopathy (BSE) was detected in hundreds of cattle born after the ban. To study the role of MBM, animal fat, and dicalcium phosphate on the risk for BSE after the feed ban, we conducted a spatial analysis of the feed industry. We used data from 629 BSE cases as well as data on use of each byproduct and market area of the feed factories. We mapped risk for BSE in 951 areas supplied by the same factories and connection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…The potential for cross-contamination is heightened by the potential for low-dose exposure causing infection; in an oral exposure study it was shown that cattle could become infected by as little as 1 mg of brain homogenate [63]. A statistically significant relationship between the pig density in a region and BAB cases has also been found in subsequent studies on both the GB data [58] and for other countries including Northern Ireland, France, Switzerland, and Spain [1,3,26,30,55], supporting this initial hypothesis of cross-contamination of cattle feed with feed intended for pigs, and possibly poultry; a spatial study on feed factories confirmed recently the use of MBM in monogastric feed as a risk factor for BSE [51]. Further evidence on the BAB cases arising from the feedborne source has been provided by Sheridan et al [57], where a spatial relationship between feed-producers and BSE cases was found.…”
Section: Routes Of Infectionsupporting
confidence: 67%
“…The potential for cross-contamination is heightened by the potential for low-dose exposure causing infection; in an oral exposure study it was shown that cattle could become infected by as little as 1 mg of brain homogenate [63]. A statistically significant relationship between the pig density in a region and BAB cases has also been found in subsequent studies on both the GB data [58] and for other countries including Northern Ireland, France, Switzerland, and Spain [1,3,26,30,55], supporting this initial hypothesis of cross-contamination of cattle feed with feed intended for pigs, and possibly poultry; a spatial study on feed factories confirmed recently the use of MBM in monogastric feed as a risk factor for BSE [51]. Further evidence on the BAB cases arising from the feedborne source has been provided by Sheridan et al [57], where a spatial relationship between feed-producers and BSE cases was found.…”
Section: Routes Of Infectionsupporting
confidence: 67%
“…The Bovine Spongiform Encephalopathy (BSE) is a noncontagious neurodegenerative disease in cattle. This sudden and unexpected disease threatened bovine production in Europe and has been intensively studied, in particular, for spatial patterns [Abrial et al (2005a), Allepuz et al (2007), Paul et al (2007)]. It is transmitted by meat and bone meal.…”
Section: 2mentioning
confidence: 99%
“…Geography and topography are not, however, important explanatory factors for the disease which should rather be related to local agricultural traditions. In these regions there is a high density of monogastric species [Abrial et al (2005a)], for example, pigs and poultry, and meat and bone meal were used to feed these species [Paul et al (2007)]. It is suspected that the BSE risk can be explained by cross-contamination with an ingredient used in poultry or pig feed.…”
Section: 2mentioning
confidence: 99%
“…A statistically significant relationship between pig density and the number of BAB cases has been shown in France as well as in other countries, including Northern Ireland, Switzerland and Spain (Allepuz et al, 2007;Denny & Hueston, 1997;Doherr et al, 2002;Schwermer & Heim, 2007), supporting the hypothesis of cross-contamination of cattle feed with feed intended for pigs and possibly poultry. To analyze in greater detail at which stages of the feed chain cross-contaminations may have played a role in the spread of BSE in France, a spatial study of feed factories was carried out that confirmed the use of MBM in monogastric feed as a risk factor for BSE (Paul et al, 2007). In parallel, a case-control study at the farm level demonstrated that the use of compound feed for young cattle, and the presence of poultry operations on farms, using compound feed, were risk factors for BSE, thus providing further evidence of the role of compound feed in the risk of BSE.…”
Section: Epidemiological Studies Epidemiological Analysis Of the Routmentioning
confidence: 99%
“…The underlying hypothesis was that the different local contexts of feed processing factories contributed to varying capacities to manage crosscontaminations. Quantitative data collected from March 2004 to June 2005 by the Ministry of Agriculture (Direction générale de l'alimentation) in 1014 feed factories in France (Paul et al, 2007) were used to describe the local contexts of feed production in France. In addition, qualitative data were collected in Bretagne in June 2006.…”
Section: Insight From Geography On the Feed Industrymentioning
confidence: 99%